Dynamic ultrasound imaging applications to quantify musculoskeletal function - Sikdar, S.; Wei, Q.; Cortes, N. (Exercise and Sport Sciences Reviews, 2014)
For the field of physical activity (PA) and cancer survivorship to flourish, researchers must demonstrate compelling links between cancer variables and PA. In this article, I propose a simple framework that highlights four major propositions that largely define the field of PA and cancer survivorship. I also provide examples of my own research that have tested each of these propositions.